2023
DOI: 10.3390/nu15061400
|View full text |Cite
|
Sign up to set email alerts
|

PRO-DEMET Randomized Controlled Trial on Probiotics in Depression—Pilot Study Results

Abstract: There is a pressing need to identify new treatment options for depression and its comorbidities. Depression often coexists with metabolic complications, and the two may share a pathophysiological overlap, including inflammation and microbiota changes. Microbiota interventions (e.g., probiotics) may represent a safe and easy-to-use treatment option as an adjunctive therapy in patients only partially responsive to pharmacologic treatment. (1) Objective: The paper presents the results of a feasibility and pilot s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…Most of the studies included in this review support the beneficial effects of probiotics. Kazemi et al [ 46 ] demonstrated a significant decrease in BDI score (17.39–9.1) compared to placebo (18.18–15.55) ( p = 0.042), after an 8-week use of a probiotic supplement as the main treatment, while Gawlik-Kotelnicka et al also demonstrated clinically significant improvement in MADRS and QoL (quality of life) scores [ 63 ]. On the same basis, Schaub et al [ 45 ] showed significant improvement in depression at the 8-week follow up, with a remission rate of 55% in the probiotics group compared to a 40% in the placebo group, but only for the one subgroup with high compliance of a short-term, high-dose intake of probiotics as a supplementary treatment for depression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies included in this review support the beneficial effects of probiotics. Kazemi et al [ 46 ] demonstrated a significant decrease in BDI score (17.39–9.1) compared to placebo (18.18–15.55) ( p = 0.042), after an 8-week use of a probiotic supplement as the main treatment, while Gawlik-Kotelnicka et al also demonstrated clinically significant improvement in MADRS and QoL (quality of life) scores [ 63 ]. On the same basis, Schaub et al [ 45 ] showed significant improvement in depression at the 8-week follow up, with a remission rate of 55% in the probiotics group compared to a 40% in the placebo group, but only for the one subgroup with high compliance of a short-term, high-dose intake of probiotics as a supplementary treatment for depression.…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al [ 54 ] also reported correlations between fluctuations in IL-6 levels and the abundance of the genus Akkermansia . Additionally, Gawlik-Kotelnicka et al [ 63 ] reported reduced inflammation marker levels due to probiotics usage, while Miyaoka et al [ 60 ] also suggested that C. butyricum M588 may have significant anti-inflammatory effects. Furthermore, recent data from Yang et al [ 51 ] showed that serum corticotrophin-releasing hormone (CRF) levels and heart rate of healthy controls remained unchanged after taking probiotics suggesting that taking probiotics has no effect on the body’s physiological CRF.…”
Section: Resultsmentioning
confidence: 99%
“…The general characteristics of the included studies are outlined in Table S4. Trials were published between 1996 and 2023, and were carried out in Asia, 12,27–31,77–81,84–229 Europe, 230–262 America,…”
Section: Resultsmentioning
confidence: 99%
“…However, more participants were recruited considering the possible attrition rate. Due to significant difficulties in enrolling patients with MetS (as reported in the pilot study [31]), we decided to perform a two-arm study controlling for metabolic abnormalities.…”
Section: Participantsmentioning
confidence: 99%
“…Based on the above, the PRO-DEMET randomized controlled trial protocol was constructed [30]. Then, the pilot study was performed with convincing results regarding the feasibility of a whole-scale study [31]. Importantly, several alterations to the study plan were introduced and explained in the publication of the pilot study results, which are discussed throughout the current manuscript.…”
Section: Introductionmentioning
confidence: 99%